OVERVIEW OF VILLAGE FINANCIAL MANAGEMENT AND IMPLICATIONS FOR ACCOUNTABILITY - Duwi Agustina; Ayu Wulandari (Integrated Journal of Business and Economics (IJBE), 2020)
The purpose of this study was to test empirically the influence of the variable of village apparatus capability, organizational commitment, implementation of SISKEUDES and BPD supervision on village financial management. This study also aims to determine the effect of village financial management on accountability in Tanjung Pandan District, Belitung Regency. The data used in this study are primary data obtained from distributing questionnaires directly to members of Village institutions in Tanjung Pandan District which are related to village financial management, consisting of the Village Government, Village-Owned Enterprises (BUMDesa) and Community Empowerment Institutions (LPM). The research sample was determined by the saturated sampling method (census) totaling 140 people. Statistical analysis used the SmartPLS version 3.2.8 program with the PLS-PM (Path Modeling) structural equation model. The results showed that the capability of the village apparatus had no significant positive effect on village financial management. Organizational commitment has a significant positive effect on village financial management, the implementation of SISKEUDES has a significant positive effect on village financial management and BPD supervision has a significant positive effect on village financial management. In addition, the research results also show that village financial management has a significant positive effect on accountability.